FINE STRUCTURE OF LISTERIA MONOCYTOGENES - Edwards, Mercedes R. (1963)
Edwards, Mercedes R. (New York State Department of Health, Albany) and Roy W. Stevens. Fine structure of Listeria monocytogenes. J. Bacteriol. 86:414–428. 1963.—Cells of Listeria monocytogenes, at different stages of growth, were fixed with osmium tetroxide and treated with uranyl acetate. The material was dehydrated in alcohol, embedded in prepolymerized methacrylate, and studied in thin sections. In most of the micrographs, the plasmalemma (or plasma membrane) showed a pattern of three dense lines, each ca. 25 A thick, alternating with two light zones, each ca. 30 A thick. The outer light zone was regularly bridged by strands of dense material, and the inner one was not. The dense line at the edge of the cytoplasm was not always discernible because of its similarity in density with the ground cytoplasm, although it could be easily demonstrated in lysed cells and in protoplasts. The latter were found to be limited by a pair of dense lines, each ca. 25 A thick, bounding a light core ca. 30 A thick. This structure corresponds to a “unit” membrane, but it represents only a part of the plasmalemma of the intact cell; it was therefore interpreted as being more complex than a single unit membrane. Intracytoplasmic membranes of various configurations were clearly shown to be extensions of the plasmalemma. They may branch repeatedly and anastomose to form a complicated honeycomb-like organelle or organelles of different appearances, sometimes lamellate. The lamellar bodies are envisioned as resulting from spiraled ingrowths. The various kinds of ingrowths of the plasmalemma were designated “plasmalemmosomes” to indicate their origin; however, some of these organelles in Listeria were similar to those described in different bacteria by other authors. Plasmalemmosomes have been found in both aerobically and anaerobically grown cells. Another outstanding feature in many micrographs was the nucleoid, which contains dense fibrils measuring 25 to 50 A in diameter. These fibrils frequently appeared to be coiled and were of the order of magnitude ascribed to deoxyribonucleic acid molecules.